Penerapan Model Project Based Learning (PjBL) Berbasis Pendidikan Lingkungan Hidup terhadap Hasil Belajar IPAS Siswa Kelas IV Sekolah Dasar - Priska Ayu Nawang Wulan; Rita Kusumah (Jurnal Pendidikan, Sains, Geologi, dan Geofisika (GeoScienceEd Journal), 2026)
Teacher-centered instruction in the IPAS (integrated Science and Social Studies) subject has left many fourth-grade students at SD Negeri 2 Bayuning struggling to reach the minimum mastery criterion, a concern made more urgent by ongoing environmental pressures in the Kuningan area, including uncontrolled waste. This study set out to determine whether combining Project Based Learning (PjBL) with Environmental Education could raise both students' cognitive achievement and their environmental care attitude. Using a quantitative, Quasi-Experimental approach with a Nonequivalent Control Group Design, the researcher worked with 39 fourth-graders split into an experimental group (n = 20) and a control group (n = 19). The experimental group carried out a hands-on "seed paper" recycling project under the PjBL framework, whereas the control group followed the school's usual teaching routine. Multiple-choice tests, a Likert-type questionnaire, and observation sheets supplied the data, which were then examined through normality and homogeneity checks, an Independent Sample t-test, and N-Gain calculations. The t-test produced a significance value of 0.000 (below the 0.05 threshold), and the experimental group's N-Gain reached 72.40 percent (fairly effective) against only 38.51 percent (ineffective) for the control group. A similar gap appeared for environmental attitudes, where the treatment group settled into the Very Caring category while the comparison group remained one level lower, at Caring. Taken together, these results suggest that pairing PjBL with an environmental theme is a workable way to lift both academic understanding and ecological awareness among elementary IPAS learners.